Woodworth, Ed., The Loyal, True, Brave - America’s Civil War Soldiers; Ashdown & Caudill, The Mosby Myth - A Confederate Hero In Life And Legend - Long, Michael (Teaching History: A Journal of Methods, 2004)
Clearly, there is no shortage of source material when studying the American Civil War. Where does a teacher or student begin to sort through the thousands of volumes that have been published on America’s most-studied conflict? Steven E. Wood worth, associate professor of history at Texas Christian University, has assembled a collection of essays intended to serve as an introduction, "to present the Civil War to both formal and informal students of the conflict and to select brief excerpts from some of the numerous books that have been written about the soldiers."